Global cheesemaking technology : cheese quality and characteristics - Papademas, Photis; Bintsis, Thomas (Wiley, 2018)
Global Cheesemaking Technology: Cheese Quality and Characteristics reviews cheesemaking practices, and describes cheeses and the processes from which they are manufactured.In addition, the book examines new areas to stimulate further research in addition to the already established knowledge on the scientific principles on cheesemaking.